2012
DOI: 10.1590/s2176-94512012000300022
|View full text |Cite
|
Sign up to set email alerts
|

Orthopedic treatment of Class III malocclusion with rapid maxillary expansion combined with a face mask: a cephalometric assessment of craniofacial growth patterns

Abstract: Objective: The aim of this prospective study was to assess potential changes in the cephalometric craniofacial growth pattern of 17 children presenting Angle Class III malocclusion treated with a Haas-type expander combined with a face mask. Methods:Lateral cephalometric radiographs were taken at beginning (T 1 ) and immediately after removal of the appliances (T 2 ), average of 11 months of treatment. Linear and angular measurements were used to evaluate the cranial base, dentoskeletal changes and facial grow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…The extent of circumaxillary suture disjunction with a 5-week Alt-RAMEC protocol, demonstrated in a cat model, was significantly greater (94.4% vs. 64.8%) than with a 1-week RME protocol [ 6 ]. The amount of maxillary protraction has been reported to be 4–6 mm in 5 months under the Alt-RAMEC protocol [ 1 , 3 ], whereas it was 1.5–3.0 mm in 10 to 12 months under the RME protocol [ 7 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…The extent of circumaxillary suture disjunction with a 5-week Alt-RAMEC protocol, demonstrated in a cat model, was significantly greater (94.4% vs. 64.8%) than with a 1-week RME protocol [ 6 ]. The amount of maxillary protraction has been reported to be 4–6 mm in 5 months under the Alt-RAMEC protocol [ 1 , 3 ], whereas it was 1.5–3.0 mm in 10 to 12 months under the RME protocol [ 7 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…[ 20 ] and Tagawa et al . [ 21 ] in their cephalometric studies also concluded that the Alt-RAMEC protocol along with reverse pull headgear treatment was advantageous in the correction of mild-to-moderate maxillary retrusion in Class III patients. Their studies showed that the forward movement of the maxilla was without maxillary incisor movement.…”
Section: Discussionmentioning
confidence: 99%
“…Um aspecto inerente ao processo de tratamento para a má oclusão classe III é que o sucesso do seu tratamento é bastante perceptível em pacientes na fase do crescimento puberal, pois a presença da maturidade esquelética no indivíduo pode dificultar o processo de correção, mesmo com o uso da máscara (Tagawa et al 2012;Dores et al 2023). O protocolo de tratamento pode incluir ainda o uso de um splint acrílico para auxiliar na expansão maxilar e a expansão maxilar com disjuntor tipo Hyrax associado à máscara modelo Petit tem se mostrado eficaz na correção desse tipo de caso clinico de má-oclusão (Flores;Aguiar, 2021).…”
Section: Introductionunclassified